(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, it is considered on the basis of a small study that the Task-based approach is also of great importance in the formation and improvement of lexical skills, based on this approach, it is possible to improve lexical skills using the Scavenger hunt technique. The article also highlights the importance of this technique in the formation of lexical skills of 5th grade schoolchildren.